Adolescents’ Knowledge and Perception of Traditional Food Products Typical of Banten Gipang PD Laila - Ekawardhani, Y A; Maulia, Holif (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study’s aim was to find out how much adolescents in Banten Province knew about the brand of traditional snack gipang PD Laila and how they viewed the visual presentation of its goods. This study employed a descriptive methodology that included observation, personal conversation, and literature review. Gipang as traditional snack are thought to be impacted by modern trends relating to the creation of new companies and different sorts of snacks. According to the outcomes of direct discussion with the owner, PD Laila’s gipang items are among those that conflict with these conditions. Teenagers were also given an online survey to complete about the traditional snack gipang, the product brand, and the packaging. The findings indicated that although most youths in Banten Province were familiar with the traditional gipang snack, they were unable to name the brand of gipang as traditional snack. The majority of respondents do not know the brand name of PD Laila’s gipang traditional snack and have a negative opinion of the product packaging, which influences their decision to buy traditional cuisine. The marketing of PD Laila’s gipang items needs to be updated because they are thought to not have an appealing presentation or appearance. The study’s findings suggest that in order for PD Laila’s gipang traditional snack products to be recognizable and draw in young people, package improvements and product advertising media are required.